7ab-3a^2b^2+7+8ab^2+3a^2b^2-3-7ab =(7ab-7ab)+(-3a^2b^2+3a^2b^2)+7-3=4 3x^3-3x^2-y^2+5y+x^2-5y+y^2 = 3x^3+(-3x^2+x^2)+(5y-5y)+(-y^2+y^2 )=3x^3-2x^2
化简整式两题(1)7ab-3a^2b^2+7+8ab^2+3a^2b^2-3-7ab(2)3x^3-3x^2-y^2+5
2个回答
相关问题
-
化简(3a^3-ab+7)-(5ab-4a^2+7) 其中a=2 b=3/1 求值 化简 6( x^-3X)-2(X-2
-
3a^2-5a∧2+ab-b^2-7ab+7b^2+3a∧2=?化简
-
化简:(1)-9y+6x2+3(y−23x2);(2)5(a2b-3ab2)-2(a2b-7ab2);
-
(3a^2-ab+7)-2(-2a^2+ab+3.5)化简
-
1.先化简再求值,3a^2-3ab/a^2-2ab+b^2,a=8,b=7
-
-2a^3b+8a²b²-8ab^3 (7x²+2y²)²-(2x&s
-
^3ab^2-5ab^3-3ab^2+5b^3a-8a^3b^2+8a^2b^3化简
-
整式的计算:(1)-3a2+2ab-4ab+2a2(2)5(3a2b-ab2)-3(ab2+5a2b)(3)化简求值:当
-
整式的计算(1)-3a2+2ab-4ab+2a2(2)5(3a2b-ab2)-3(ab2+5a2b)(3)[1−2x/3
-
a+b=2,ab=-3,则整式2(a-2b+ab)+(a+7b-3ab)的值是_____________.